Rancang Bangun Sistem Informasi Penjualan dan Pembelian Berbasis On-Premise (Windows-Based) - Muhamad Fahmi Nugraha; Moh Abdul Aziz Aziz; M Ryzki Wiryawan Wiryawan (Masoem University, 2025)
The digitalization of business processes has become an urgent need for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. However, technology implementation at the MSME level still faces limitations related to infrastructure, cost, and digital literacy. This research develops an on-premise (Windows-based) sales and purchase information system at Ibu Siti's Store in Cicalengka as a pragmatic solution to connectivity and reliability constraints. The system was designed using the Agile methodology, enabling iterative and adaptive development tailored to user needs. The on-premise platform was selected to support offline operations, integration with local cashier hardware, low implementation costs, and high stability within a small business environment. The system is equipped with role-based access control, automated database backups, and features for transaction and inventory reporting. Test results indicate an improvement in transaction efficiency and data accuracy. This research also outlines future development opportunities, including barcode scanner integration, minimum stock notifications, and cloud synchronization, to align with the trend toward smarter, more connected MSME digitalization.